Hematological and Extra-Hematological Manifestations of Parvovirus B19 Disease - Zeybek, Cengiz; Bolat, Ahmet; Gürsel, Orhan; Eker, İbrahim; Kürekçi, Ahmet Emin (Journal of Pediatric Infectious Diseases, 2023)
Objective Parvovirus B19 (PVB19) is a virus that can present with many hematological and extra-hematological findings. Its prognosis is relatively good in immunocompetent patients, but severe disease may develop in immunocompromised patients. We retrospectively reviewed a series of children who presented with PVB19 during a 6-year period at our institution.Methods Nine children with positive polymerase chain reaction and serological test results for PVB19 were studied. Their demographic data, atypical clinical and laboratory findings, treatment regiments, clinical course, and prognosis were noted.Results The hematological abnormalities associated with PVB19 were anemia, neutropenia, and thrombocytopenia, and the extra-hematological abnormalities were systemic lupus erythematosus-like syndrome, hemophagocytic lymphohistiocytosis, and acute kidney injury. All patients had good outcomes with no significant sequelae.Conclusion This case review suggests that clinicians should not consider PVB19 only as a cause of hematological events; they should also be alert to the possibility that it may cause extra-hematological diseases.
Keywords: parvovirus B19; hematological; extrahematological